2020
DOI: 10.32479/irmm.9017
|View full text |Cite
|
Sign up to set email alerts
|

Rational Antecedent Framework of Brand Satisfaction in the Industrial Market: Assessing Rational Perceived Quality and Rational Perceived Value Roles

Abstract: Referring to the traditional paradigm, the industrial decision process is most likely influenced by rational aspects; is this perspective still relevant? The purpose of this paper is to explore further the role of rational satisfaction's antecedents, particularly perceived quality and perceived value. This study conducts a literature review and an in-depth analysis of 10 papers published by reputable Scopus index publishers, with respondents from various industries and time horizon of the last 5 years. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
2
8
0
1
Order By: Relevance
“…According to Mbango (2019), customer value has an influence on customer satisfaction. Samudro et al (2020) as well as Susanti et al (2020) also confirmed that perceived value exerts a stronger influence on customer satisfaction in the chemical industry. Based on these empirical findings, we hypothesised: H1: Customer-perceived value has a significant effect on customer satisfaction.…”
Section: Relationship Between Customer-perceived Value and Customer Satisfactionmentioning
confidence: 55%
See 1 more Smart Citation
“…According to Mbango (2019), customer value has an influence on customer satisfaction. Samudro et al (2020) as well as Susanti et al (2020) also confirmed that perceived value exerts a stronger influence on customer satisfaction in the chemical industry. Based on these empirical findings, we hypothesised: H1: Customer-perceived value has a significant effect on customer satisfaction.…”
Section: Relationship Between Customer-perceived Value and Customer Satisfactionmentioning
confidence: 55%
“…For example, Ashraf et al (2018) conducted a case study on five lines of business engaged in services, hotels, hospitals, education, and banks in Pakistan, reporting a significant effect of service quality on customer satisfaction. Furthermore, service quality has been found as an important determinant of customer satisfaction in retail banking (Caruana, 2002), the game industry (Wu, 2014), chemical industry (Susanti et al, 2020), international medical travel sector (Han & Hyun, 2015), and in cargo services (Arief et al, 2019). This has resulted in the following hypothesis: H3: Service quality has a significant effect on customer satisfaction.…”
Section: Relationship Between Service Quality and Customer Satisfactionmentioning
confidence: 99%
“…The demand for digital reading is also based on users' perceived needs. Needs of this kind are often regarded as rational needs by researchers (Susanti et al 2020). Rational needs can be simply understood as a kind of demand generated by concluding, after deliberation, that one really needs a certain product (Self et al 2008).…”
Section: A) Perceived Needs Of Digital Readingmentioning
confidence: 99%
“…Perceived quality is the customer's evaluation of the recent consumption, and industrial buyers evaluate custom products and services (Turkyilmaz et al, 2013); if the customer's perceptions toward quality aspects of products and services are positive, then brand quality shall shape the buyer's evaluation of brand value (Michell et al, 2001;Taylor et al, 2007). In the industrial relationship, the buyer's expectations about brand quality are often used as a basis for the perceived value assessment (Gordon et al, 1993;Jalkala & Keränen, 2014;Susanti et al, 2020b). Therefore, rational brand quality is expected to have a positive direct effect on the value, as stated in the following hypothesis.…”
Section: Rational Brand Qualitymentioning
confidence: 99%